PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA CONSUMER GOODS SECTOR - Prafidhya Dwi Yulianto; Lilik Ambarwati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The purpose of this research is to know the influence of Working CapitalManagement on Profitabilty in Consumers Goods listed on the Bursa EfekIndonesia (BEI) aims to analyze the influence of woring capital in the from of:Cash Turnover, Account Receivable Turnover, and Inventory Turnover toProfitability (Return On Asset) at Consumers Goods Sector. This research methoduses multiple linear regression analysys with the help of SPSS 23.00 softwarewhich is used to see the inflyence between the independent variables in the fromCash Turnover, Account Recevaible Turnover, and Inventory Turnover to ReturnOn Asset (ROA)). The sample of this research is 31 consumer goods sector in2015-2018, so there are 124 annual report obtained through purposive sampling,then analyzed using multiple linear regression methods. The result showed thadbased on the F test, the independent variable had an effect on the ROA, it isindicated of 6.765 and significance of 0.000, overall the independent variable wasable to eaplain the effect 59,60%. While based on the partial t test, shows that thevariable Cash Turnover, Account Recevaible Turnover, and Inventory Turnoverhas a positive and siginificant effect on Profitability.